Behavioural Intention of Islamic Crowdfunding among SMES: Extending UTAUT ‎Theory with Trust, Trialability and Technology Readiness - Engku Hassan Ashari, Engku Huda Mursyidah; Abdul Rahman, Aisyah (International Journal of Accounting and Economics Studies, 2025)
Islamic crowdfunding offers a Shariah-compliant financing alternative that is particularly ‎relevant for Bumiputera SMEs facing limited access to conventional funding. Despite its ‎potential, adoption remains low, highlighting a gap in understanding behavioral drivers. This ‎study extends the UTAUT model by incorporating perceived trust, trialability (as a mediator), ‎and technology readiness (as a moderator) to examine behavioral intention toward Islamic ‎crowdfunding. A quantitative survey was conducted among Bumiputera SME owners and ‎analyzed using PLS SEM Version 4. The findings indicate that social influence, facilitating ‎conditions, trust, and trialability significantly impact behavioral intention, while technology ‎readiness enhances the link between trust and behavioral intention to use Islamic ‎crowdfunding. Performance expectancy has no significant effect, and effort expectancy ‎negatively influences behavioral intention, though this turns positive when mediated by ‎trialability. This study contributes to Islamic fintech literature and provides insights for ‎policymakers and platform developers‎.